POLEMIK HARUN NASUTION DAN H.M. RASJIDI DALAM MISTISISME ISLAM - Syakur, Abdus (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
Harun Nasution is known as a pioneer of academic Islamic studies in Indonesia, including the study of Islamic mysticism. However, H.M. Rasjidi criticized Harun Nasution. H.M. Rasijidi by assuming his views deviate from Islamic teachings. Based on this polemic, this paper focused on two main topics. First, the problem of legitimacy of Islamic mysticism. Second, al-ittiḥâd. This paper used a descriptive-analysis method with reference to the works of Harun Nasution and H.M. Rasjidi as primary data. Then, the data is compared by referring to supporting references to analyze their views further. This paper shows two conclusions according to the focus of this paper. First, H.M. Rasjidi considers that Islamic mysticism is not in accordance with Islamic teachings, because it emphasizes the aspects of influence from outside Islam. While, Harun Nasution viewed mysticism as an important aspect of Islam, because it was considered to have a strong source from the al-Qur’ân dan Ḥadîth. Second, Harun Nasution views that al-ittiḥâd is the main goal of Islamic mysticism which philosophically describes the bond of servants to God. While, H.M. Rasjidi rejects the concept of al-ittiḥâd and is deemed deviating from Islamic teachings because it is considered to equate God with beings.